1996
DOI: 10.1177/0266242696151004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Productivity and Quality in Small and Medium Enterprises: Cases and Analysis

Abstract: At The Time of Writing, All four authors, A. Gunasekaran, P. Okko, T. Martikainen, and p. Yli-oli were with the school of busines studes, University of Vaasa, Finland. In most cases small and medium enterprise prodcue their own product but at the same time they prodcue items for large-scale industries. These create certain interdependencies among SMEs and between them and large-scale industries in order to improve the competitiveness of SEMs in exporting. During recent year large-scale industries have undergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 5 publications
2
35
0
4
Order By: Relevance
“…Also, Wilkes and Dale (1998) concluded that SMEs focus more directly on the knowledge of the market environment than in strategic planning to design improvement plans in business. Accordingly, it can be considered in general that SMEs are less bureaucratic and more flexible than big enterprises (Gunasekaran et al, 1996). That is why it is easier the adoption and implementation of KM activities (Moffet & McAdam, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Also, Wilkes and Dale (1998) concluded that SMEs focus more directly on the knowledge of the market environment than in strategic planning to design improvement plans in business. Accordingly, it can be considered in general that SMEs are less bureaucratic and more flexible than big enterprises (Gunasekaran et al, 1996). That is why it is easier the adoption and implementation of KM activities (Moffet & McAdam, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…This need comes from increased agility in larger organizations, which enables them to erode traditional SME niche markets. Furthermore, increased internationalization has encouraged some SMEs to operate in more competitive global markets, where continuous innovation is a prerequisite [Gunasekaran et al (1996)]. Throughout this paper a broad managerial perspective is taken to innovation, as distinct from solely that of technical development.…”
Section: Innovation In High-tech Smesmentioning
confidence: 99%
“…Moreover, Wilkes & Dale, (1998) suggest that SMEs are more focused directly on market changes, as distinct from strategic plans for devising business improvements. In this manner, smaller organizations are less bureaucratic and more flexible in comparison to larger organizations (Gunasekaran et al, 1996). In the SME environment there is much 'closer proximity to the customer' (Barrier, 1994).…”
Section: Macro-environmentmentioning
confidence: 99%